The Feasibility of Interactive Multimedia Development in Children' Story of Character Education-Based in 7th Grade Students of Junior High School Panca Budi Medan - Wenny Anggraeni; Syahnan Daulay; M. Oky Ferdian Gafari (BIRCU, 2019)
The media serves to direct students to gain various learning experiences. The aim of this study is to know the feasibility of interactive multimedia development in children' story of character education-based. Sources of data in this study were obtained from: 1) Respondents: 7th grade students of Junior High School Panca Budi Medan which amount to 23 students, 2) Informants: validators, students and Indonesian language teachers of Junior High School Panca Budi Medan. The results of the feasibility of learning media validation by instructional media design experts was declared